Feminine Romantic Style dengan Aplikasi Songket Balai Panjang Payakumbuh - Fitri, Qurratha Laila; Rahmanita, Nofi; Aryadi, Mirda (Style : Journal of Fashion Design, 2023)
Feminine romantic is one of basic fashion styles that is synonymous with the impression of a dress that is calm, sweet, and dominated by soft design lines, the colors used in this clothing style are synonymous with soft colors, and the use of materials such as silk, borkat, crepe, silk and chiffon. To realize the feminine romantic style in clothing creation, the Balai Panjang songket was chosen as a medium applying this style to become ready-to-wear clothing. Clothing that designed is aimed at teenage women aged 19-25 years, and adult women aged 26-35 years, to make it easier for users to choose clothes for work, travel, recreation, and parties. The purpose of creating this clothing is to be able to design clothing with the theme of feminine fomantic style with the Balai Panjang songket application, then demonstrate it in the form of a fashion show, so that the designed work can be socialized to general public. Clothing with a type of feminine romantic style has never been made with the Balai Panjang Songket, so with the creation of this work it can be become a reference for the creation of work of feminine romantic style for the future. In creating the work of this final project, the artist uses creation methods such as preparation, design, embodiment to the presentation of the work carried out. The process of creating clothing uses standard boutique sewing technique, namely by using a lining material, so that the clothes are the resulting impression give a neat, and clean. The results of the design source ideas for feminine romantic style are in the form of ready to wear, ready to wear deluxe and haute couture clothing.